2000
DOI: 10.1007/s004050000236
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of sudden hearing loss associated with a high signal in the labyrinth on unenhanced T1-weighted magnetic resonance imaging

Abstract: We report on five patients with high signals in the labyrinth on unenhanced magnetic resonance imaging who developed sudden hearing loss and vertigo. Weissman et al. (1992) suggested the possibility that such high signals were caused by hemorrhage. We assessed these patients using audiograms, caloric tests, and auditory brainstem responses to investigate the possibility of inner ear hemorrhage. Most of the patients were found to have severe and irreversible impairment of both cochlear and vestibular function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 3 publications
(2 reference statements)
1
40
0
Order By: Relevance
“…3,4,13,15 Loss of water signal intensity in high resolution T2-weighted images (eg, DRIVE, constructive interference in the steady state) also is reported for LH; 15 however, we did not detect abnormality on high-resolution T2-weighted images. Contrast-enhanced TI-weighted imaging can exclude tumors such as schwannomas and hemangiomas that show intense and localized enhancement.…”
Section: Original Researchmentioning
confidence: 50%
“…3,4,13,15 Loss of water signal intensity in high resolution T2-weighted images (eg, DRIVE, constructive interference in the steady state) also is reported for LH; 15 however, we did not detect abnormality on high-resolution T2-weighted images. Contrast-enhanced TI-weighted imaging can exclude tumors such as schwannomas and hemangiomas that show intense and localized enhancement.…”
Section: Original Researchmentioning
confidence: 50%
“…Some series report 100% of affected patients having persistent SNHL on follow-up. 9 Two cases were reported to show improved hearing: Shinaharo et al documented an average 30dB hearing gain after steroid therapy on a non-profound down-sloping threshold curve 6 and Salomone et al reported an average 20dB hearing gain after unspecified medical therapy. 5 This patient's recovery was restricted to higher frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…When reviewing the literature, only two cases reporting improvement in hearing function could be found. 5,6 The authors describe the clinical, functional and imagiological findings in a patient with rheumatoid arthritis who suffered labyrinthine haemorrhage and partly recovered cochlear and vestibular functions.…”
Section: Introductionmentioning
confidence: 99%
“…7 In an exceptional case of enlarged endolymphatic duct and sac syndrome, 3D-FLAIR without contrast revealed endolymphatic hydrops by visualizing the re‰ux of hemorrhagic ‰uid from the enlarged sac to the cochlea and vestibule. 8 Although inner ear hemorrhage has been reported in many cases of sudden deafness, such as in patients with leukemia and those receiving anticoagulant therapy, [9][10][11] we do not believe that focal inner ear hemorrhage, such as that conˆned to the ampulla of the semicircular canal, has been reported.…”
Section: Introductionmentioning
confidence: 93%